The seat of a commercial company incorporated under Polish law versus cross-border transmission of the company to another EU Member State - Tomasz Słapczyński (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
In the paper the author makes an attempt at defining and interpreting the notion of the seat of a commercial company. The issue is vital especially when the shareholders of a company decide to transfer its the seat to another country. The doctrine and judicature are not uniform in the way they define the notion of a company’s seat what gives rise to qualification problems with respect to the fact whether the seat is transferred as subject to discretion or maybe the seat of the company is understood as its corporate (business) office where the actual business activity is being conducted, or perhaps it is its registered office. The problem in a direct way impacts the principle of freedom of business activity. The aim of the paper is to develop a uniform standing on when it is possible to proceed with cross-border transmission of a company’s seat. The author conducts linguistic and functional analysis of Polish and European regulations, doctrinal views as well as judicature of Polish courts and the Court of Justice of the European Union (CJEU). The author of the paper suggests that it should be assumed that the seat of a commercial company is, in fact, its registered office, what in consequence will cause fewer problems in the process of its transfer to another country. The paper tries to confirm this assumption through the analysis of relevant domestic and EU regulations, the judicature of Polish courts and of CJEU.